Model uncertainties in foundation design - Tang, Chong; Phoon, Kok-Kwang (Boca Raton : CRC Press, 2021)
'Geotechnical design codes worldwide are increasingly being directed to reliability-based design, for which the characterization of model uncertainty is a critical element. This practical book is based on a global load test database which provides information on the foundation, site or soil investigation, and load test results'--
Includes bibliographical references and index.
Keywords: Foundations -- Design and construction -- Data processing; Soil mechanics -- Data processing; Dead loads (Mechanics) -- Mathematical models; Measurement uncertainty (Statistics); Piling (Civil engineering) -- Mathematical models